Relationship Between Transabdominal Measurements of Prostate Volume and Anthropometric Measurements among Male Residents in Ondo State - Fatukasi, J. I.; Osho, S. E.; Oyamakinde, S. O.; Ogunsemoyin, A. (British Journal of Healthcare and Medical Research, 2022)
Introduction: The prostate gland is a major site of diseases like prostatitis, benign prostatic hyperplasia and carcinoma of the prostate. Growth and enlargement of prostate can be predicted by prostate volume in the future. The prostate gland volume are influenced by a number of factors which includes age, body mass index (BMI), waist circumference (WC) and ethnicity. Aim: To study the relationship between anthropometric measurements and transabdominal measurements of prostate volume among male Residents in Ondo State. Method: A cross-sectional descriptive study was carried out at Ultrasound Department, University of Medical Sciences Teaching Hospital, Ondo, Ondo state with 200 healthy adults categorized into 4 age groups 1,2,3 and 4 i.e 20-50 years, 51-60 years, 61-70years, >71 years. Three categories of BMI was formed which are Healthy (18 to 25 kg/m2), Overweight (>25 to 29 kg/m2), Obese (≥30 kg/m2). Data analysis was done using SPSS version 20. Post hoc- LSD Fishers test was applied to make comparison between means of different groups. Univariate analysis was used to test the linear association among the variables. . P-value < 0.05 was considered significant. Results: Mean age of the subject in this study was 46.3 ± 17.0 years (Table 1). Age group was divided into group 1, 2, 3 and 4 i.e 20-50 years, 51-60 years, 61-70years, >71 years with 125, 29, 24 and 22 subjects respectively (Table 2). The BMI was classified into three groups which includes normal weight, over weight and obese with 100, 65 and 35 subjects respectively. The mean BMI in the study was 25.8 ± 4.61. Significant positive correlation was seen between prostrate volume and Age and positively with BMI. The correlation coefficients were (r=0.017) and (r=0.062) respectively. Conclusion: Age plays a significant role in the determination of prostate volume. The prostrate volume increases as the age increases. Also BMI has a contributing factor to change in prostate volume as the Obese people have an increase prostate volume.